Jouer avec des mots, des objets et des êtres : une approche anthropologique du jeu - Wendling, Thierry (My University, 2007)
Though play is a universal phenomenon found in all known societies there is a huge number of different ways to play. Several examples of play or games are considered here to explain how people manage their relationships with words, objects and beings. In the first instance, with ritual or ludic insults and riddles, meaning is constructed through an agonistic social process. In the second, objects are used to symbolize and materialize rules, as during eating contests where the competitors are not permitted to drink more than a glass of water. Finally, confrontation with real or virtual opponents (in online games) is a good way to identify theories of mind, because players attribute agency to virtual beings.